OPTIMALISASI PERAN SUKUK DALAM MENUMBUHKAN SEKTOR RIIL DI INDONESIA - Antasari, Rina; Azwari, Peny Cahaya; Martiwi, Dyah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2017)
Indonesia as one of the world's rice importer is inversely proportional to its reputation as the state Agriculture. This is because the lack of support from the government. In the latest budget, the government allocated only 1.3% of the total budget for the agribusiness sector. Faced with these conditions, the Islamic Financial System has tools specifically related instruments with real sector called Sukuk/ Bond Sharia.